Corruption in Batak Na Raja Perspective - Simanjuntak, Nelson; Silalahi, Fernando; Tampubolon, Manotar (Journal of Universal Community Empowerment Provision, 2024)
This article describes the results of anti-corruption legal counseling in Lumban Dolok Village, Silaen District, Toba Regency, North Sumatra. This counseling aims to raise public awareness about the dangers of corruption and the importance of integrity, by adopting Batak Na Raja cultural values that emphasize anti-corruption attitudes. Corruption is viewed from the perspective of Batak Na Raja as behavior that not only violates the law, but also the customs and morality of the Batak community. A person's motive for committing corruption is often related to economic needs, existing opportunities, and weak supervision. GONE (Greed, Opportunity, Need, and Exposure) and Fraud Triangle (pressure, opportunity, and rationalization) theories are used to analyze the motives and driving factors of corruption. This counseling emphasized that, in accordance with the values of Batak Na Raja, the Toba people are expected to uphold honesty, responsibility, and transparency. By understanding and internalizing these values, society is expected not only to reject corruption but also actively prevent it. This counseling succeeded in instilling an understanding that corruption damages social and economic order, and is contrary to the Batak philosophy of life that upholds honesty and honor. It is hoped that, through a cultural approach and intensive legal education, the Toba people can become the frontline in eradicating corruption, strengthening good governance, and realizing sustainable welfare in their region.